Hydrothermal carbonization of cellulose and xylan into hydrochars and application on glucose isomerization. (10th November 2019) - Sheng, Kuichuan; Zhang, Shen; Liu, Jianglong; E, Shuang; Jin, Caidi; Xu, Zenghua; Zhang, Ximing
Abstract: Hydrochar microsphere as clean and facile carbon materials have great potentials to be used in biomass valorization for producing value-added chemicals. In this study, the hydrochars obtained from cellulose and xylan were prepared. The effect of hydrothermal conditions on hydrochars' chemical composition, thermal stability and the porosity obtained from cellulose and xylan were evaluated. In order to explore the application of the hydrochar in biofuel production, the cellulose derived hydrochar supported Al catalyst (Al-Cel-HTC) was prepared by one-step hydrothermal process for catalysis glucose isomerization. We found distinct physicochemical properties between cellulose and xylan derived hydrochar. The specific surface area ( S BET ) of cellulose derived hydrochar (118 m 2 /g) is significantly higher than that of xylan derived hydrochar (28 m 2 /g). The hydrochars are composed of carbonaceous microspheres as evidenced by SEM. The catalytic performance of Al-Cel-HTC was investigated. Results shown that 77.8 mol/% selectivity of glucose to fructose can be obtained in aqueous by the catalyst. The SEM-EDS images of the catalyst shown the strong crystal-hydrochar microsphere interaction benifit in diminishing the agglomeration of hydrochar microsphere. The BET specific surface area and crystal structure (AlO(OH) and Al2 O3 ) of hydrochar supported aluminum catalyst have positive correlation with the catalytic selectivity. Graphical abstract: Image 1 Highlights: Xylan requires significantly lower temperature compared to cellulose for HTC process. Cellulose derived hydrochar has more than 4 times larger surface area than xylose derived hydrochar. Cellulose and xylan derived hydrochars shows distinct microscopic morphology. Different depolymerization and condensation mechanisms were revealed for cellulose and xylan HTC processing. The novelty hydrochar microsphere support Al catalyst for glucose isomerization shown that the catalyst have a great potential for biomass valorization.